12(12n-4)=12-10n

Simple and best practice solution for 12(12n-4)=12-10n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12(12n-4)=12-10n equation:


Simplifying
12(12n + -4) = 12 + -10n

Reorder the terms:
12(-4 + 12n) = 12 + -10n
(-4 * 12 + 12n * 12) = 12 + -10n
(-48 + 144n) = 12 + -10n

Solving
-48 + 144n = 12 + -10n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '10n' to each side of the equation.
-48 + 144n + 10n = 12 + -10n + 10n

Combine like terms: 144n + 10n = 154n
-48 + 154n = 12 + -10n + 10n

Combine like terms: -10n + 10n = 0
-48 + 154n = 12 + 0
-48 + 154n = 12

Add '48' to each side of the equation.
-48 + 48 + 154n = 12 + 48

Combine like terms: -48 + 48 = 0
0 + 154n = 12 + 48
154n = 12 + 48

Combine like terms: 12 + 48 = 60
154n = 60

Divide each side by '154'.
n = 0.3896103896

Simplifying
n = 0.3896103896

See similar equations:

| 8t+1695=5255 | | 2(1-x)=-6-2x | | 6x^3+2x^2-15x-5=0 | | 7(7+6b)= | | x=3119.42-0.05x | | -(7x+3)-(-6y-8)=3 | | -x=-31 | | a+b+c=3.03 | | -6(4x-4)=-10-7x | | 2b^2-98=0 | | 9x^2-29x+5=-1 | | 2b-21=30 | | -7x-1=-2(4+4x) | | 29x-35y=8 | | 2x^2-33x+133=0 | | 6(-3b-4)=26-8b | | 2y-11=9 | | -4+7-2x+10x= | | 4p+12=-3-5(5p-3) | | 6x-11=3x+37 | | y^2-2=0 | | 8m+2+4m=12m+2 | | 3+8x=2(4x+2) | | 41y=5(8y-y) | | 4k+38=-2(-6k+1) | | x=3119.42-0.025x | | 7y-8-10y+6= | | 2(y+3)-4(2y+1)=y-3(2+y) | | 11+3q=14+2q | | -2(8n+2)-8n=32-6n | | -12m+4=8m-6 | | -2x-15=-(6x+7) |

Equations solver categories